Systematic Literature Review Identifying Core Genera in the Gut Microbiome of Rainbow Trout (Oncorhynchus mykiss) and Species‐level Microbial Community Analysis Using Long‐Read Amplicon Sequencing - Mio Takeuchi; Kazuhiro Sugahara (Aquaculture, Fish and Fisheries)
ABSTRACT Rainbow trout (Oncorhynchus mykiss) is an important fish in global aquaculture. Various feed additives to suppress disease or reduce fish meal use have been studied. These manipulations influence the gut microbiome, which is considered to be linked to host health. However, a consensus remains to be established on the healthy gut microbiome composition. This study aimed to identify core genera in the gut of rainbow trout via a systematic review of 39 articles and determine candidate core species using long‐read amplicon sequencing targeting the full‐length 16S rRNA gene. Mycoplasma, Aeromonas, Clostridium, Deefgea, Streptococcus, Cetobacterium, Lactobacillus, Lactococcus, Methylobacterium, Corynebacterium, Shewanella and Staphylococcus were identified as core genera in the autochthonous gut microbiome of rainbow trout based on the systematic review. In addition, through long‐read amplicon sequencing, we identified candidate core species of the core genera of rainbow trout, such as Latilactobacillus sakei, Clostridium gasigeness, Deefgea piscis and Pseudomonas yamanorum. These findings may ultimately contribute to the development of manipulation technologies in aquaculture.